Boom and Burst in Housing Market with Heterogeneous Agents - Alessandro Spelta; Guido Ascari; Nicolò Pecora (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
We study the housing market using a partial dis-equilibrium model in which the rational expectations hypothesis is relaxed in favor of an agent-based approach. The chartist-fundamentalist mechanism allows for the behavioral foundation of the expectations, the endogenous development of bubbles and contributes to replicate the recent house price dynamics. We also analyze the role of the interest rate during the boom and, anchoring the interest rate to the change in house price, we investigate the possibility to reduce the volatility and the distortion in the price dynamics.
Keywords: 330